Efficacy of school-based career guidance interventions: A review of recent research - Sharapova, Nargiza; Zholdasbekova, Saule; Arzymbetova, Sholpan; Zaimoglu, Omer; Bozshatayeva, Gulshat (Journal of Education and e-Learning Research, 2023)
This paper aims to examine the impacts of career guidance interventions on school students’ career-related skills, knowledge and beliefs by combining relevant empirical studies conducted in the last 10 years. A random-effects meta-analytic technique was employed for this purpose. After screening, electronic databases using pre-defined eligibility criteria, nine studies involving a total of 1,433 participants were included in the final meta-analysis. The analysis yielded a weighted mean effect size of 0.42 (95% confidence interval = 0.19, 0.65; z = 3.61, p < 0.01) which may be construed as a moderate-to-high effect size with a significant difference between the treatment and control conditions at post-treatment. As a result, post-test career-related outcomes in students who received career guidance were significantly higher than in non-guidance groups. The results suggest that career interventions may provide some modest developmental progression in school-age children and adolescents particularly through improving learners’ career decidedness and attitudes such as future time perspective. These findings might have strategic implications for policy and practice. This paper extends past research on career guidance effectiveness by identifying the combined effect size of relevant career interventions.